Housing and health outcomes: evidence on child morbidities from six Sub-Saharan African countries - Kanyiva Muindi; Samuel Iddi; Hellen Gitau; Blessing Mberu (BMC, 2023)
Abstract Background The connection between healthy housing status and health is well established. The quality of housing plays a significant role in infectious and non-communicable as well as vector-borne diseases. The global burden of disease attributable to housing is considerable with millions of deaths arising from diarrheal and respiratory diseases annually. In sub-Saharan Africa (SSA), the quality of housing remains poor although improvements have been documented. There is a general dearth of comparative analysis across several countries in the sub-region. We assess in this study, the association between healthy housing and child morbidity across six countries in SSA. Methods We use the Demographic and Health Survey (DHS) data for six countries where the most recent survey collected health outcome data on child diarrhoea, acute respiratory illness, and fever. The total sample size of 91,096 is used in the analysis (representing 15, 044 for Burkina Faso, 11, 732 for Cameroon, 5, 884 for Ghana, 20, 964 for Kenya, 33, 924 for Nigeria, and 3,548 for South Africa). The key exposure variable is healthy housing status. We control for various factors associated with the three childhood health outcomes. These include quality housing status, residency (rural/urban), age of the head of the household, mother's education, mother's BMI status, marital status, mother's age, and religious status. Others include the child's gender, age, whether the child is from multiple or single births, and breastfeeding status. Inferential analysis using survey-weighted logistic regression is employed. Results Our findings indicate that housing is an important determinant of the three outcomes investigated. Compared to unhealthier housing, healthy housing status was found to be associated with reduced odds of diarrhoea in Cameroon [Healthiest: aOR = 0.48, 95% CI, (0.32,0.71), healthier: aOR = 0.50, 95% CI,(0.35,0.70), Healthy: aOR = 0.60, 95% CI, (0.44,0.83), Unhealthy: aOR = 0.60, 95% CI, (0.44,0.81)], Kenya [Healthiest: aOR = 0.68, 95% CI, (0.52,0.87), Healtheir: aOR = 0.79, 95% CI, (0.63,0.98), Healthy: aOR = 0.76, 95% CI, (0.62,0.91)], South Africa[Healthy: aOR = 0.41, 95% CI, (0.18, 0.97)], and Nigeria [Healthiest: aOR = 0.48, 95% CI,(0.37,0.62), Healthier: aOR = 0.61, 95% CI,(0.50,0.74), Healthy: aOR = 0.71, 95%CI, (0.59,0.86), Unhealthy: aOR = 0.78, 95% CI, (0.67,0.91)], and reduced odds of Acute Respiratory Infection in Cameroon [Healthy: aOR = 0.72, 95% CI,(0.54,0.96)], Kenya [Healthiest: aOR = 0.66, 95% CI, (0.54,0.81), Healthier: aOR = 0.81, 95% CI, (0.69,0.95)], and Nigeria [Healthiest: aOR = 0.69, 95% CI, (0.56,0.85), Healthier: aOR = 0.72, 95% CI, (0.60,0.87), Healthy: aOR = 0.78, 95% CI, (0.66,0.92), Unhealthy: aOR = 0.80, 95% CI, (0.69,0.93)] while it was associated with increased odds in Burkina Faso [Healthiest: aOR = 2.45, 95% CI, (1.39,4.34), Healthy: aOR = 1.55, 95% CI, (1.09,2.20)] and South Africa [Healthy: aOR = 2.36 95% CI, (1.31, 4.25)]. In addition, healthy housing was significantly associated with reduced odds of fever among children in all countries except South Africa [Healthiest: aOR = 2.09, 95% CI, (1.02, 4.29)] where children living in the healthiest homes had more than double the odds of having fever. In addition, household-level factors such as the age of the household head, and place of residence were associated with the outcomes. Child-level factors such as breastfeeding status, age, and sex, and maternal-level factors such as education, age, marital status, body mass index (BMI), and religion were also associated with the outcomes. Conclusions The dissimilarity of findings across similar covariates and the multiple relations between healthy housing and under 5 morbidity patterns show unequivocally the heterogeneity that exists across African countries and the need to account for different contexts in efforts to seek an understanding of the role of healthy housing in child morbidity and general health outcomes.